Assessing the resistance and bioremediation ability of bacterial species isolated from mine tailings of Philex Mines, Benguet, Philippines to copper and chromium - Buscayno, Marie Chemantha Alexandria C.; Raguindin, Erica Joy D.; Tempra, Fritzie Maye A.
Bacterial populations associated with Philex Mines' tailings pond in Itogon, Benguet, Philippines were isolated and cultured. Isolates were screened for tolerance to copper and chromium at concentrations 0.5mM, 6.0mM, 10.0mM, 15.0mM, 30.0mM, and 50.0mM. At 50.0mM concentration of copper and chromium, a total of 14 aerobic, copper and chromium tolerant bacteria were cultured and selected for molecular identification. Analysis of 16SrDNA revealed that isolates were phylogenetically affiliated with Phyla Firmicutes, Actinobacteria, and Proteobacteria, represented by the genera Bacillus, Staphylococcus, Micrococcus, and Pseudomonas. The isolates were further characterized based on their efficiency to bioremediate the heavy metals copper and chromium. Results showed that Bacillus circulans was the most efficient bioremediator of chromium at 50.0mM which reduced the metal present in solution by 36.25 and Staphylococcus lentus for chromium at 20.0mM with 25.18%. For copper remediation, Micrococcus luteus was able to bioremediate the said metal by 82.08% at 5.0mM and Bacillus subtilis by 23.83% for 20.0mM copper. The study showed the presence of bacterial strains that can be exploited for use in bioremediation of copper and chromium -- Author's abstract.